Optimizing the Functions of the Village Consultative Body in the Realization of Democracy in Motabang Village : (Study of Bolaang Mongondow Regency Regional Regulation No. 6 of 2018 on Village Consultative Body) - Djenaan, Fildzah Muzdalifah; Kasim, Nur Mohamad; Sarson, Mohamad Taufiq Zulfikar (Reformasi Hukum, 2024)
This research examines how local regulations regulate the functions of the Village Consultative Body (BPD) and whether these rules have been implemented properly. The research method used is empirical-sociological juridical with a statutory and conceptual approach. This research not only focuses on the applicable legal rules, but also looks at how the law is implemented and affects social life through field data collection. The results showed that BPD has a legislative function in discussing and agreeing on village regulations with the Sangadi (village head), accommodating and channeling community aspirations, and overseeing the performance of the Sangadi. The results showed that implementing the BPD function in Motabang Village was not optimal. The BPD tends to carry out its duties as a formality, especially in discussing village regulations and supervising the performance of the Sangadi. The inhibiting factors include the BPD members' low understanding of regulations, lack of community participation, and conflicts of personal interest. To improve the effectiveness of BPD performance, it is necessary to increase the capacity of members through training, increase community participation, and strengthen independence in carrying out supervisory functions.